Manhunts : a philosophical history - Chamayou, Grégoire (Princeton University Press, 2012)
Touching on issues of power, authority, and domination, Manhunts takes an in-depth look at the hunting of humans in the West, from ancient Sparta, through the Middle Ages, to the modern practices of chasing undocumented migrants. Incorporating historical events and philosophical reflection, Grégoire Chamayou examines the systematic and organized search for individuals and small groups on the run because they have defied authority, committed crimes, seemed dangerous simply for existing, or been categorized as subhuman or dispensable.